Educational Museum Guides Prepared by Teacher Candidates - UTKUGÜN, Ceren; Kurtdede Fidan , Nuray; Yıldırım, Ramazan (Journal of History Culture and Art Research, 2024)
In this research, educational museum guides prepared by teacher candidates for museums in Turkey; the courses that were linked and the learning areas/units that were most linked were examined through achievements, legal process documents, evaluation forms and activities. The research is a qualitative research and was carried out using the document analysis technique. The study group of the research consisted of 43 museum guides prepared by 66 teacher candidates studying in the classroom teaching undergraduate program at a state university in the fall semester of the 2023-2024 academic year. Content analysis technique was used to analyze the data obtained. As a result of the research, it was seen that teacher candidates made associations with nine different courses in the museum guides they prepared. The courses with the most associations were life sciences and Turkish, followed by science, social studies, mathematics, visual arts, religious culture and ethics, music, human rights, citizenship and democracy courses, respectively. In the museum guides they prepared, teacher candidates included documents regarding the legal process that must be followed in order to organize tours; they included examples of a museum trip pre-survey, a museum trip evaluation post-survey, and a worksheet for a museum trip. In addition, the guides included 29 different activities, including activities focused on art and creativity, educational and instructive, entertaining and focused on developing mental skills and activities focused on observation and understanding. The majority of teacher candidates stated that the process of preparing a museum guide contributed to them. The fact that the process is fun and instructive, that it enables learning and understanding, and that it develops skills are among these contributions. Some teacher candidates encountered difficulties during the process, such as not being able to relate it to outcomes, not being able to access sufficient information about museums and having difficulties in designing activities. As a result of the research, it is recommended to conduct studies on the preparation of similar guides regarding museums and other out-of-school learning environments with prospective teachers studying in different undergraduate programs who have the potential to use museums for educational purposes, and to conduct quasi-experimental studies to test the applicability of the prepared guides.